The Olympian affair - Butcher, Jim, 1971- (Butcher, Jim, 1971- Cinder spires, 2023)
"The fate of the Cinder Spires may be decided by crossed swords in the next exhilarating fantasy adventure from the author of the Dresden Files, in this New York Times bestselling series of noble families, swordplay, and airships. For centuries the Cinder Spires have safeguarded humanity, rising far above the deadly surface world. Within their halls, aristocratic houses rule, developing scientific marvels and building fleets of airships for defense and trade. Now, the Spires hover on the brink of open war. Everyone knows it's coming. The guns of the great airship fleets that control the skies between the last bastions of humanity will soon speak in anger, and Spire Albion stands alone against the overwhelming might of Spire Aurora's Armada and its new secret weapon--one capable of destroying the populations of entire Spires. A trading summit at Spire Olympia provides an opportunity for the Spirearch, Lord Albion, to secure alliances that will shape the outcomes of the war, and to that end he dispatches privateer Captain Francis Madison Grimm and the crew of the AMS Predator to bolster the Spirearch's diplomatic agents. It will take daring, skill, and no small amount of showmanship to convince the world to stand with Spire Albion--assuming that it is not already too late"--